Merancang Kurikulum Pendidikan Agama Kristen Milenial (Menjawab Tuntutan Kecakapan Abad 21 di Era Milenial) - Esther Bessie; Bernadetha Nadeak; Lamhot Naibaho (Journal on Education, 2023)
The millennial era with all its progress presents its own needs and challenges in the field of education, including Christian religious education. Not just needs and challenges, Christian religious education also needs to find opportunities so that its duties towards fulfilling the needs of the millennial generation can still be carried out. It is necessary to design a millennial Christian religious education curriculum that is based on Bible teachings, which can meet the development of 21st century competencies without neglecting all the components that must be integrated in it. This article emphasizes the Christian religious education curriculum to build 21st century skills that are integrated with character building and literacy competence, as well as paying attention to the characteristics of the millennial generation. This research was carried out using descriptive qualitative research methods, by collecting important information from various print and digital sources. The author finds that it is necessary to design a millennial Christian religious education curriculum to answer the challenges of 21st century competence. This curriculum design is useful for preparing meaningful 21st century learning in order to produce a generation of golden Indonesian Christians who are competent in the 21st century and have strong character as a generation who fear God